2020
DOI: 10.1139/facets-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial segregation and habitat partitioning of bobcat and Canada lynx

Abstract: Harvest records suggest that the abundance of bobcats ( Lynx rufus) has increased and the leading edge of their distribution has spread northward, while the trailing edge of the Canada lynx ( Lynx canadensis) range has contracted in Ontario, Canada. There has been a debate about whether these closely related felids might compete in areas of sympatry, but there is little research on sympatric populations of bobcat and lynx. Both species are found on the north shore of Lake Huron in Ontario, Canada, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Northwestern shores of Lake Superior received less snow than the northern shores of Lake Huron. Currently, on the north shores of Lake Huron intermediate forest cover is still important to bobcat, since bobcat in this area are almost exclusively found in rural communities within 50 km of urban centers (Marrotte et al, In Review). The increasing density of human disturbances such as roads, rail lines, urban areas, rangeland, and agricultural land would have also further amplified colonization, because road plowing and snow compaction would have become more frequent, which allowed bobcat to move around and hunt more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Northwestern shores of Lake Superior received less snow than the northern shores of Lake Huron. Currently, on the north shores of Lake Huron intermediate forest cover is still important to bobcat, since bobcat in this area are almost exclusively found in rural communities within 50 km of urban centers (Marrotte et al, In Review). The increasing density of human disturbances such as roads, rail lines, urban areas, rangeland, and agricultural land would have also further amplified colonization, because road plowing and snow compaction would have become more frequent, which allowed bobcat to move around and hunt more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, bobcat sightings, road kills, and individuals incidentally harvested by trappers have become more common in the region (Marrotte, Bowman, & Morin In Review; Roberts & Crimmins, ; Woolf & Hubert, ). There is evidence that bobcat populations are spreading into areas where they were thought to be absent (Linde, Roberts, Gosselink, & Clark, ; Woolf & Hubert, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This spatial relationship itself indicates that the bobcat is not responsible for the range contraction in the southeastern zone, since it is rarely found there. Recent finer scale studies suggested segregation between lynx and bobcat (Marrotte et al 2020b, Morin et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…As high Firmicutes to Bacteroides ratios correspond to larger body size and fat stores [19,35], we hypothesized that larger Firmicutes to Bacteroides ratios would be correlated with larger home ranges, as individuals building up fat stores for winter would generally use more space to forage. This relationship may be impacted by resource distribution, as specialists prefer homogenously distributed resources, while generalists prefer heterogeneously distributed resources, which can impact space use [36]. Consequently, we hypothesized that relationships between proportional habitat use and the gut microbiome would be stronger in specialists as they have a more restricted niche with deviations from this having larger consequences, whereas generalists can make use of a variety of habitat areas.…”
Section: Introductionmentioning
confidence: 99%